Mapping and Serodiagnostic Application of a Dominant Epitope within the Human Herpesvirus 8 ORF 65-Encoded Protein - Pau, Chou-Pong (American Society for Microbiology, 1998)
A dominant epitope within the human herpesvirus 8 (HHV8) ORF 65-encoded protein was mapped to an 8-amino-acid (aa) sequence (RKPPSGKK [aa 162 to 169]) by an amino acid replacement method. Using a 14-aa peptide (P4) encompassing this epitope as the antigen, we developed an enzyme immunoassay for HHV8 antibodies. The presence of P4 antibodies in a panel of 61 human serum specimens was highly correlated with biopsy-confirmed Kaposi’s sarcoma. The homologous Epstein-Barr virus peptide derived from BFBR3-encoded protein did not interfere with the assay, suggesting that P4 is specific for HHV8.